Producción comercialización y rentabilidad de plantas de cacao (Theobroma cacao) en vivero en el sitio la saiba del Cantón Palenque. - Nieto Anchundia, Victor Hugo (2011)
This research was conducted in Cantonese and Mocache Palenque, Los Rios province, with an average score of 2000 to 2400 mm. Has 4 to 8 dry months per year. The average temperature ranges between 22 and 34 ° C, relative humidity ranges from 72 to 80%. It pursued the following objectives: To analyze the processes of production, distribution, marketing and benefit in the management of cocoa nursery plants, describe the technical characteristics of the production process of cocoa plant nursery, analyze marketing channels cocoa plants in nurseries in the area of study and determine the profitability of the production of nursery plants. A survey in the area of influence, taking a representative sample of the nursery industry for a total of 10, the information collected was analyzed to determine the current status of activity relating to the mass production of plants. Of the 370000 plants produced, 32% are national genotypes, while 68% of the NCC 51. The substrate is used more regularly is the compound with soil + manure + rice chaff. For his part, 89% of the seeds were sown directly in the holster, while 11% pre-germinated before being placed in the holster. The most commonly used fertilizer is 10-30-10 complete fertilizer, insect pests that attack are: Lepidoptera (larvae defoliating) by 17% and aphids (aphids) to a lesser extent this is 0.6% and whose control is performed with Chlorpyrifos (dose, 2 cc / l water) and Diazinon (dose, 2 ml / lt water) respectively. As the disease who achieved greater presence was the witch's broom with 7% and for control using copper-based fungicides (dose, 5 g / l water). The use of chemical products to fertilize and control pests and diseases was 70%, 100% and 100% respectively, the distribution and sale of plants is done by 59% at the site of the nursery, while 41% delivered at home. The cost price varies between $ 0.3 and 0.34 for clone CCN 51 and between 0.35 and 0.40 for National clones. The sale price for the CCN 51 ranges between $ 0.50 and $ 0.55, while the national is between $ 0.60 and $ 0.65. The current bid is 370,000 plants a year, and estimated for the next 5 years reaches a value of 1850000 plants. For its part, demand is estimated at 3009699 plant investment cost to produce plants is 370000 106716.58, Internal Rate of Return (IRR) reached a value of 102%, demonstrating that this project shows high profitability. Net Present Value (NPV) reached a figure of $ 434,191.23. The Benefit-Cost is $ 1.90.